Silêncios diegéticos e a composição musical audiovisual - Marina Marcon Moreira (2024)
In an attempt to raise questions about silences in audiovisual media, this research considers the concept of diegetic silences as noises present in scenes with a fundamental role in narrative construction. We will begin this journey with an investigation of studies about silences. Based on definitions of the term and works by authors such as John Cage, we will address silences composed of noises, as the world – just like us – is full of them. Transferring this perception to the audiovisual universe, we will interpret this category through the lenses of Michel Chion and Claudia Gorbman's Sound-Image theories, which bring the idea that silence can be created in various ways. By relating the concepts presented with filmic examples, the text reinforces the idea that, while in the real world the sounds intrinsic to silences are already ready, in the audiovisual world silences are created through the manufacture of noises. These noises, which in the research encompass all sound effects, have different roles in the story. When designed specifically for the scene with narrative intent, they give rise to diegetic silences – silences within the diegesis. Therefore, we understand that diegetic silences, when interacting with other sound elements present in the track, such as music, create immersion in the story. The study proposes five categories of diegetic silences that connect to music in various ways to illustrate this interaction: silence as a character, silence as a musical element, silence as a narrative marker, hybrid silence, and silence creating electroacoustic music. Finally, to apply these definitions of diegetic silence in practice, the last chapter concludes with four studies and production details, all of which are intended as compositional tests in which diegetic silences interact with music at various levels.